Betwixt and Between: Yup’ik Combat Soldiers and the Burden of Wars - Linda Green (Antropologia, 2013)
The article examines the dual burdens faced by Yup’ik men from the Yukon-Kuskokwim Delta who serve in the US military. It highlights the historical and contemporary violence experienced by these indigenous communities and how their military service intertwines with their marginalized status. The narrative underscores the complex motivations behind their enlistment, often driven by a search for economic stability and familial tradition. It also explores the cultural dissonance and trauma that accompany their return to civilian life, revealing deep-rooted systemic inequities.